Kemampuan Berpikir Reflektif Matematis dalam Menyelesaikan Soal Pemecahan Masalah Matematika - Annisa, Annisa; Isnaniah; Aprison, Wedra; M. Imamuddin (Universitas Cokroaminoto Palopo, 2025)
This research was motivated by observations at SMP Negeri 7 Bukittinggi. The observation results show that there are still many VII grade students who have low mathematical reflective thinking skills. One of the reasons for the low mathematical reflective thinking ability of students is because they are not accustomed to working on non-routine problems that contain indicators of mathematical reflective thinking ability. The purpose of this study was to describe the mathematical reflective thinking ability of students in class VII.2 SMP Negeri 7 Bukittinggi in the 2024/2025 academic year in solving mathematical problems. This type of research is descriptive quantitative used to provide a clear picture of the level of student ability in mathematical reflective thinking. The research subjects were students of class VII.2 who had been selected through purposive sampling technique and data collection using instruments in the form of mathematical problems solving tests designed to measure indicators of reflective thinking. The results showed that students' ability in mathematical reflective thinking was still concerning. Only 14.29% of students are in the sufficient category, 50% in the low category, and 35.71% in the very low category based on the results of the data analysis that has been done. The overall average of students in mathematical reflective thinking is 58.8%, which is included in the low category. This shows that most students have difficulty identifying what is known and asked in the problem (reacting), comparing and connecting old problems with new problems (comparing/elaborating), and reflecting and re-evaluating their answers before drawing conclusions (contemplating).